Understanding Kuwaiti women entrepreneurs and their adoption of social media: a study of gender, diffusion, and culture in the Middle East - Alghaith, Shaikhah, author; Kodrich, Kris, advisor; Champ, Joseph, committee member; Martey, Rosa Mikeal, committee member; Anderson, Karrin Vasby, committee member; Hirchi, Mohammed, committee member (Colorado State University. Libraries, 2016)
The growing number of small businesses owned by Kuwaiti women in recent years is an indication of a new progress that Kuwaiti women are achieving. This study through the lens of Diffusion of Innovations theory examined why and how Kuwaiti women entrepreneurs adopt social media. It investigated the attributes of social media that made social media appealing to be adopted by Kuwaiti women entrepreneurs. It also investigated the pros and cons associated with social media when used as a marketing tool. This study specifically looked at Facebook, Twitter, and Instagram comparing these three types of social media. This study integrated concepts such as gender, entrepreneurship, social media, Diffusion of Innovations theory, and culture. The snowball sample of this qualitative study included in-depth interviews with owners of 20 businesses which revealed detailed data examining women’s entrepreneurship and their adoption and use of social media as a marketing tool. Kuwaiti women entrepreneurs were asked in 2014 to answer 18 questions that included inquiries regarding Rogers’ (2003) five attributes of innovation: relative advantage, compatibility, complexity, trialability and observability. The results showed that most Kuwaiti women entrepreneurs in this study prefer using Instagram, the photo and video sharing social networking platform, over Facebook and Twitter when marketing to their customers. Findings also revealed Rogers’ attributes associated with adopting an innovation, such as relative advantage, complexity, and observability, apply to adopting Instagram as a marketing tool by Kuwaiti women entrepreneurs. Kuwaiti women entrepreneurs adopt and incorporate Instagram in their marketing strategy because of Instagram’s photo-sharing nature (relative advantage), ease of use (complexity), and popularity (observability). This study’s findings also unveiled the perceived pros of using Instagram as a marketing tool – Instagram is like a photo album, it enlarges the circle of customers, it is widely used, and it is suitable for smaller businesses. However, the study also showed several cons to Instagram – including that products may not be what they seem and that the business owners have to deal with rude and discouraging comments. The women entrepreneurs also worry about providing unique content. They worry that their accounts will be stolen or lost and their products’ photos may be copied. They also wonder how long Instagram will be the preferred social media.